Implementación de un centro de mantenimiento aeronáutico en la ciudad de Guayaquil - Salas Luzuriaga, Edgar (2010)
This abtract sets out general ideas of a Repair Station complete and total customer satisfaction by providing services in accordance with quality standards established by the various agencies and entities such as DGCA (Directorate General of Civil Aviation of Ecuador) and FAA (Federal Aviation Administration) Aircraft Maintenance is the technical activity that aims to ensure that an aircraft is maintained in a condition of "Airworthiness" is legal and technical skills which should have an aircraft to fly in condition for safe operation , so that: Let there be safety or physical integrity, including their parts, components and subsystems, their implementation capacity and employment characteristics, which leads the aircraft effective operation in the use (corrosion, breakage, loss fluids, etc..) until the next maintenance over its lifetime. Transport both passengers and cargo, as a result of migration, increased tourism and increased exports to foreign markets operate, with high occupancy levels.